The Molecular and Immunological Landscape in Nasopharyngeal Carcinoma ( NPC ) Differs by Somatostatin Receptor 2 ( SSTR2 ) Expression - Dara Bracken‐Clarke; Elisabetta Xue; Harris Krause; Tolulope Adeyelu; Mark G. Evans; Dilara Akbulut; Martha Quezado; Nishant Gandhi; Alex Farrell; Heloisa P. Soares; Emil Lou; Minh Phan; et al. (Cancer Medicine, 2026)
ABSTRACT Somatostatin receptor 2 is expressed in nasopharyngeal carcinoma (NPC). We report genomic and transcriptomic analysis results of 163 NPC cases, demonstrating that somatostatin receptor 2 ( SSTR2 ) gene expression in EBV‐positive and in EBV‐negative NPC correlated with genomic alterations and an inflamed microenvironment. Median SSTR2 expression was 6.52 transcripts per million (TPM), ranging from 0.59 TPM (Quartile 1 [Q1], 18.2% EBV‐positive) to 35.79 TPM (Q4, 82.9% EBV‐positive). PIK3CA (20.51%) and CYLD (10.53%)/ NFKBIA (12.82%) mutations were enriched in SSTR2 ‐Q1 versus ‐Q4. Tumor mutation burden was negatively correlated ( R = −0.27, p < 0.001) with SSTR2 , while PD‐L1 tumor proportion score (2% vs. 92.5% [ SSTR2 :Q1 vs. Q4], p < 0.001) and T‐cell inflamed score correlated with SSTR2 expression ( R = 0.53, p < 0.001). B‐cells, M1 macrophages, CD8+ T‐cells, Treg cells, and dendritic cells were enriched in SSTR2 ‐Q4, while neutrophils were prominent in SSTR2 ‐Q1. These results demonstrate a significant positive correlation between SSTR2 expression and an inflamed tumor microenvironment in NPC. This suggests that SSTR2 expression in NPC may be a clinically useful biomarker, correlating with the tumor microenvironment (including, potentially, sensitivity to immunotherapy) and its genetic profile.